Effective factors on the development of bodybuilding and fitness clubs in Mashhad, Iran - Karbaschian, Amirreza; Sadat Mirzazadeh, Zahra; Talebpour, Mahdi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to investigate the effective factors in the development of bodybuilding and fitness clubs in Mashhad, Iran. This study was practical in terms of its goals, with an exploratory and analytical implementation method, classifying it as qualitative research. A total of 27 individuals were targeted and selected as samples until theoretical saturation was reached, including athletes, coaches, managers of fitness and bodybuilding clubs, members of the academic faculty of sports sciences at universities, experts from sports departments, and seniors in the field of bodybuilding in Mashhad. For data analysis, the data coding method was employed within a grounded theory framework. Based on the results, the factors affecting the development of bodybuilding and fitness clubs in Mashhad were identified in four main categories, ten sub-categories, and seventy-two components, according to expert opinions and a literature review in this field. These factors included: 1) Facility and infrastructure factors, 2) Financial and economic factors, 3) Professionalism factors, 4) Human resource factors, 5) Event factors, 6) Scientific and educational factors, 7) Organizational and managerial factors, 8) Motivational factors, 9) Media factors, and 10) Cultural-social factors. By creating and facilitating this model, the development steps for Mashhad's fitness clubs will be implemented to better align with future implementation conditions.